A Weavable and Scalable Cotton‐Yarn‐Based Battery Activated by Human Sweat for Textile Electronics. Issue 7 (6th January 2022) - Xiao, Gang; Ju, Jun; Lu, Hao; Shi, Xuemei; Wang, Xin; Wang, Wei; Xia, Qingyou; Zhou, Guangdong; Sun, Wei; Li, Chang Ming; Qiao, Yan; Lu, Zhisong
Abstract: Sweat‐activated batteries (SABs) are lightweight, biocompatible energy generators that produce sufficient power for skin‐interface electronic devices. However, the fabrication of 1D SABs that are compatible with conventional textile techniques for self‐powered wearable electronics remains challenging. In this study, a cotton‐yarn‐based SAB (CYSAB) with a segmental structure is developed, in which carbon‐black‐modified, pristine yarn and Zn foil‐wrapped segments are prepared to serve as the cathode, salt bridge, and anode, respectively. Upon electrolyte absorption, the CYSAB can be rapidly activated. Its performance is closely related to the ion concentration, infiltrated electrolyte volume, and evaporation rate. The CYSAB can tolerate repeated bending and washing without any significant influence on its power output. Moreover, the CYSABs can be woven into fabrics and connected in series and parallel configurations to produce an energy supplying headband, which can be activated by the sweat secreted from a volunteer during a cycling exercise to power light‐emitting diode headlights. The developed CYSAB can also be integrated with yarn‐based strain sensors to achieve a smart textile for the self‐powered sensing of human motion and breathing. This weavable, washable, and scalable CYSAB is expected to contribute to the manufacturing of self‐powered smart textiles for future applications in wearable healthcare monitoring. Abstract : Based on the spontaneous liquid absorption and transport properties of cotton yarn, a 1D sweat‐activated battery (SAB) with great flexibility, washability, and reusability is fabricated. This cotton‐yarn‐based SAB can be perfectly integrated into fabrics via conventional textile techniques in both series and parallel configurations to function as a biocompatible and reliable power source for self‐powered human exercise sensing applications.